Probleme der Naherholung für die Prager Bevölkerung im mittleren Moldautal - Neubauer, Traute (ERDKUNDE, 1973)
In spite of their different economic systems landscapes in West European as well as in East European countries have been greatly changed by newly created recreation centres near urban agglomerations. Because of this development differences between towns and villages are tending to disappear. Though private recreation receives little support from the government in the CSSR, there are numerous weekend cottages built by the Prague population in the middle part of the Moldau Valley. This area has special advantages due to its location near the Prague agglomeration. By damming the Moldau River, several lakes were created, which form an ideal landscape for building weekend cottages as well as for house boats. As more people come to this area and the number of recreation cottages increases, the problems of infrastructure, of water supply, shopping and transport facilities as well as drainage and removal of refuse, become more difficult. On the other hand, governmental recreation facilities are in sufficient to revitalize the Prague worker’s capacity and to provide people with accomodation at a time when working hours are shortened. The author has tried in this article to show the geographic consequences of the economic development in this area.